The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1679-78253297
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Search Algorithm for Sizing Optimization of Truss Structures

Abstract: Heat transfer search (HTS) is a novel metaheuristic optimization algorithm that simulates the laws of thermodynamics and heat transfer. In this study, the HTS algorithm is adapted to truss structure optimization. Sizing optimization searches for the minimum weight of a structure subject to stress and displacement constraints. Three truss structures often taken as benchmarks in the optimization literature are selected here in order to verify the efficiency and robustness of the HTS algorithm. Optimization resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 25 publications
(102 reference statements)
0
9
0
Order By: Relevance
“…These functions concerning continuous, unbiased constrained optimization problems have varying degrees of complexity and multimodality, each with different numbers of variables and data ranges. The comparative algorithm selected in the experiment has been previously used by different people in attempts to solve various constrained optimization problems [25][26][27][28][29][30][31][32][33][34][35][36][37]. The results show good effect of these algorithms on constrained optimization problem.…”
Section: Experimental Investigationmentioning
confidence: 99%
“…These functions concerning continuous, unbiased constrained optimization problems have varying degrees of complexity and multimodality, each with different numbers of variables and data ranges. The comparative algorithm selected in the experiment has been previously used by different people in attempts to solve various constrained optimization problems [25][26][27][28][29][30][31][32][33][34][35][36][37]. The results show good effect of these algorithms on constrained optimization problem.…”
Section: Experimental Investigationmentioning
confidence: 99%
“…Since its inception, HTS has been used extensively for solving optimization problems for different applications. Degertekin et al [35] applied the HTS technique for the sizing optimization, particularly for truss structures. Three design examples were discussed in the study which demonstrated that HTS formulated better designs than those found by other state-of-the-art metaheuristic optimization methods.…”
Section: Introductionmentioning
confidence: 99%
“…The HTS algorithm has emerged as one of the most efficient methods, and it has been empirically shown to be superior to other MHAs by its authors [42]. HTS and its modified variants have been applied for solving various optimization problems [43][44][45][46][47][48][49]. However, as an efficient optimization method, the report of the applications of HTS algorithm in engineering process optimization is still rarely seen, especially in the areas of chemical process optimization.…”
Section: Introductionmentioning
confidence: 99%